2022
DOI: 10.3390/ijms231810739
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Responses of Rice Leaves to Chilling and Subsequent Recovery

Abstract: Improving chilling tolerance at the seedling stage in rice is essential for agricultural research. We combined a physiological analysis with transcriptomics in a variety Dular subjected to chilling followed by recovery at normal temperature to better understand the chilling tolerance mechanisms of rice. Chilling inhibited the synthesis of chlorophyll and non-structural carbohydrate (NSC) and disrupted the ion balance of the plant, resulting in the impaired function of rice leaves. The recovery treatment can ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Previous reports have shown that chilling stress affects numerous physiological and cellular processes in plants, including inhibiting photosynthesis, regulating calcium signals, and altering the organelle’s ultrastructure, especially the chloroplast lipid membrane [ 20 ]. Accordingly, plants employ several strategies when recovering from chilling to normal temperatures, such as inducing the expression of photosynthetic enzymes, enhancing the linoleic acid metabolism and inhibiting phenylpropanoid biosynthesis and ribosome synthesis [ 21 ]. Among these processes, maintaining the cell membrane integrity and stability is vital for chilling tolerance, and ion leakage reflects the cell membrane’s damage degree, while proline declines the electrolyte leakage level to protect membrane stability [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that chilling stress affects numerous physiological and cellular processes in plants, including inhibiting photosynthesis, regulating calcium signals, and altering the organelle’s ultrastructure, especially the chloroplast lipid membrane [ 20 ]. Accordingly, plants employ several strategies when recovering from chilling to normal temperatures, such as inducing the expression of photosynthetic enzymes, enhancing the linoleic acid metabolism and inhibiting phenylpropanoid biosynthesis and ribosome synthesis [ 21 ]. Among these processes, maintaining the cell membrane integrity and stability is vital for chilling tolerance, and ion leakage reflects the cell membrane’s damage degree, while proline declines the electrolyte leakage level to protect membrane stability [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“… 6 In addition, we can also use this gene for functional and mechanistic studies, reveal the regulatory network and signaling pathways of rice chilling tolerance, and provide clues for understanding the response and adaptation of rice to chilling stress. 29 , 44 In summary, we believe that the OsRBCS3 gene has high application value and potential in rice chilling tolerance breeding, and can provide new strategies and means for breeding new varieties or hybrid combinations that adapt to different climatic conditions and environmental requirements.…”
Section: Discussionmentioning
confidence: 97%
“…Linoleic acid is a liquid unsaturated fatty acid that plays an indispensable role in maintaining membrane integrity under cold stress [49]. Linoleic acid metabolism is significantly enhanced in the leaves of Canarium album, rice, and Rhododendron chrysanthum in response to cold stress [32,50,51]. Linolenic acid, which is converted from linoleic acid, is a precursor of JA synthesis [52].…”
Section: Discussionmentioning
confidence: 99%